Enhancing farmers income through ICAR-Farmer FIRST Programme - Kharde, P. B.; Singh, Lakhan; Deshmukh, B. A.; Sadaphal, S. S. (Indian Farming, 2019)
The project entitled â€œSocio-economic empowerment of farmers through farming system interventions for sustainable agriculture development in Ahmednagar Districtâ€ under ICAR Farmer FIRST Programme is being implemented by MPKV, Rahuri in two villages in Maharashtra, comprising 750 households. Based on the agro-ecosystem analysis, appropriate interventions in Natural Resource Management (NRM) were planned, and Integrated Farming System (IFS) components like pulses and cereals production technologies, horticultural crops along with dairy management, farm pond fishery, goat rearing and backyard poultry were implemented. On-experimentations conducted during 2016-19, showed encouraging results in crop production and increased net income to the participant farmers. On site input management was created in the village. Convergence of line departments resulted in up-scaling of innovations and technologies. The FFP has resulted in sustainable income enhancement for the farmers.